2019
DOI: 10.1002/wea.3503
|View full text |Cite
|
Sign up to set email alerts
|

How important are aerosol–fog interactions for the successful modelling of nocturnal radiation fog?

Abstract: Forecasting and modelling fog formation, development, and dissipation is a significant challenge. Fog dynamics involve subtle interactions between small‐scale turbulence, radiative transfer and microphysics. Recent studies have highlighted the role of aerosol and related cloud microphysical properties in the evolution of fog. In this article, we investigate this role using very high‐resolution large eddy simulations coupled with a newly developed multi‐moment cloud microphysics scheme (CASIM), which has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Recent studies of IOP 1 have shown that humidity and wind speed in the residual layer control the optical thickening of the fog (Smith et al, 2018), in addition to the hygroscopic growth and the fraction of CCN activated into droplets (Boutle et al, 2018). Over the same case, Poku et al (2019) recently showed, with a two-moment microphysical scheme using a single mode of CCN, that the CCN number concentration has a greater impact on fog water content than the CCN soluble fraction. The LES intercomparison will be helpful to investigate the added value of the two-moment bulk microphysical scheme LIMA using a prognostic and multimodal representation of an aerosol population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of IOP 1 have shown that humidity and wind speed in the residual layer control the optical thickening of the fog (Smith et al, 2018), in addition to the hygroscopic growth and the fraction of CCN activated into droplets (Boutle et al, 2018). Over the same case, Poku et al (2019) recently showed, with a two-moment microphysical scheme using a single mode of CCN, that the CCN number concentration has a greater impact on fog water content than the CCN soluble fraction. The LES intercomparison will be helpful to investigate the added value of the two-moment bulk microphysical scheme LIMA using a prognostic and multimodal representation of an aerosol population.…”
Section: Discussionmentioning
confidence: 99%
“…Current operational versions of MetUM use a fixed droplet number of 50 cm −1 from the surface up to 50 m and then taper to an aerosol‐dependent value at 150 m altitude. Other LANFEX studies have focused on fog microphysics (Boutle et al ., 2018; Poku et al ., 2019; Ducongé et al ., 2020). The microphysics scheme used here was evaluated for fog against the LANFEX observations and large‐eddy simulations (Boutle et al ., 2018).…”
Section: Model Observational and Case Study Detailsmentioning
confidence: 99%
“…Deep adiabatic radiation fogs are typically longer‐lived, with a greater potential to persist during the day and thus a greater impact (Price, 2011). The stability transition is sensitive to various conditions, including aerosol concentrations (Boutle et al ., 2018; Poku et al ., 2019), wind speed, and humidity (Smith et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have focused on microphysical processes in fog [3,[5][6][7][8][9][10][11][12][13][14]. Since the supersaturation in fog is low and the mean radius of fog droplets is rather small, collision and coalescence is a second order process, but the diffusional growth of the droplet population plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Third, bulk schemes, regardless of which parameterization they use, can only represent activation with a non-physical discrete transition between aerosol and cloud droplets. Recent research [9,13,14,[20][21][22] studied the influence of aerosols and microphysics on fog by using more or less advanced Eulerian cloud physic approaches. Moreover, Boutle et al [5], Maalick et al [10], Tonttila et al [23] used sectional models which allows to represent aerosol-fog interactions in a detailed and interactive way.…”
Section: Introductionmentioning
confidence: 99%